Zur Kenntnis der Biologie von Kiefernblattwespen in Bjelorußland. - Rywkin, Boris W. (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The normal egg development of pine sawflies takes place only under the conditions of a relatively dry state of the pine-needles. The outbreak of the pest is mainly caused by dry years. The brush wood and the young plants suffer more severely of the lack of moisture, and they are earlier infested by sawlies than medium aged and fellable stocks. Outbreaks of Neodiprion sertifer (Geoffroy), which has spread from North America to Europe and Asia, are particularly frequent. Among palearctic sawflies of which outbreaks are known especially Diprion pini (L.) has proved better preserved from abiotic factors and well adapted. Biological control of pine sawflies is practicable.